2022
DOI: 10.21203/rs.3.rs-1200645/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Genomics Analysis to Disentangle the Role of Genetic Variants in Major Depression

Abstract: Background: Major Depression is the leading cause of impairment worldwide. The understanding of its molecular underpinnings is key to identifying new potential biomarkers and drug targets to alleviate its burden in society. Leveraging available GWAS data and functional genomic tools to assess regulatory variation could help explain the role of Major Depression associated genetic variants in disease pathogenesis. We have conducted a fine-mapping analysis of genetic variants associated with Major Depression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Frontiers in Genetics frontiersin.org potential biomarker for MD (Yamagata and Nakagawa, 2020). Considering all eGenes together, they are enriched in their association with transcription factor regulation (Supplementary Table S9), which has already been related to MD (Zhong et al, 2019;Li X. et al, 2021;Pérez-Granado et al, 2022). The mapping of eGenes to protein interaction clusters indicated that the three sets of genes (i.e., PICS+CLPP, PICS+fasENLOC and TORUS+fastENLOC) belonged to distinct clusters and are thus likely to be involved in different biological processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frontiers in Genetics frontiersin.org potential biomarker for MD (Yamagata and Nakagawa, 2020). Considering all eGenes together, they are enriched in their association with transcription factor regulation (Supplementary Table S9), which has already been related to MD (Zhong et al, 2019;Li X. et al, 2021;Pérez-Granado et al, 2022). The mapping of eGenes to protein interaction clusters indicated that the three sets of genes (i.e., PICS+CLPP, PICS+fasENLOC and TORUS+fastENLOC) belonged to distinct clusters and are thus likely to be involved in different biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, PICS+CLPP and PICS+fastENLOC associated sets of clusters were enriched with genes associated with processes involving TF regulation as well as inflammation or neurogenesis (Supplementary Tables S10, S11). All these processes are associated with MD pathogenesis (Shadrina et al, 2018;Zhong et al, 2019;Li X. et al, 2021, Li et al, 2021Pérez-Granado et al, 2022). In general, the identified eGenes are poorly characterized yet the cluster analysis shades some light on their potential molecular associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation